Effect of Cross-Over Learning on Pupils' Academic Performance in Civic Education - Sulyman, Hafees Tosin; Jimoh, Fatimat Abiodun; Giwa, Abdulmuheez Bolaji (Bumi Publikasi Nusantara, 2025)
This study examined the effect of crossover learning on pupils’ academic performance in Civic Education in Ilorin West Local Government Area of Kwara State. A quasi-experimental design involving pre-test, post-test, and control groups was adopted. Using simple random sampling, both public and private schools were selected for the study. The instrument used Pupils' Civic Education Performance Test (PCEPT), was validated by experts and found to be reliable. Data were analyzed using Analysis of Covariance (ANCOVA). The results showed that crossover learning had a significant effect on pupils’ academic performance, with pupils exposed to crossover learning performing better than those taught with conventional methods. However, there was no significant interaction effect between crossover learning and gender or school type. The study recommends that Civic Education teachers adopt crossover learning strategies in their classrooms and that educational stakeholders organize training programs to help teachers implement this approach effectively.